KREASI KERAMIK HANDBUILT DENGAN INSPIRASI DARI ADAT PERNIKAHAN SUNDA: DESIGN OF HANDBUILT CERAMIC PRODUCTS INSPIRED BY SUNDANESE WEDDING CEREMONY - Susi Hartanto; Gaby Inetta; Geoffrey Tjakra (Universitas Trisakti, 2025)
Design of Handbuilt Ceramic Products Inspired by Sundanese Wedding Ceremony The Sundanese ethnic group, originating from West Java, possesses a rich culture with symbols and ideas that remain relevant into the modern era. The cultural symbolism serves as inspiration for creating household ceramic products using handbuilt techniques. The research process involves steps such as literature review, qualitative research, data analysis, and design development. The final products include flower vases, pitchers, and candle holders adorned with the theme of